2013
DOI: 10.1002/rnc.3008
|View full text |Cite
|
Sign up to set email alerts
|

New results on delay-dependent stability analysis and stabilization for stochastic time-delay systems

Abstract: SUMMARYThis paper investigates the problems of stability analysis and stabilization for stochastic time‐delay systems. Firstly, this paper uses the martingale theory to investigate expectations of stochastic cross terms containing the Itô integral. On the basis of this, an improved delay‐dependent stability criterion is derived for stochastic delay systems. In the derivation process, the mathematical development avoids bounding stochastic cross terms, and neither model transformation method nor free‐weighting‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Thus, during the past decades, much attention has been paid to the derivation of less conservative delay-dependent conditions. For example, some results [1,5,11,17,22,23] were established by exploiting the slack variable technique, while the other results [2][3][4]14,24,26,28] were obtained based on the Jensen inequality. Particularly, in order to further reduce the Manuscript received September 2, 2015; revised December 13, 2015; accepted February 16, 2016.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, during the past decades, much attention has been paid to the derivation of less conservative delay-dependent conditions. For example, some results [1,5,11,17,22,23] were established by exploiting the slack variable technique, while the other results [2][3][4]14,24,26,28] were obtained based on the Jensen inequality. Particularly, in order to further reduce the Manuscript received September 2, 2015; revised December 13, 2015; accepted February 16, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of time delay often degrades system performance, even leads to instability. Motivated by these facts, various research topics of time-delayed systems have emerged, for example, stability [1][2][3][4][5][6][7][8][9], stabilization [10][11][12][13][14][15][16], output control [17,18], H ∞ control and filtering [19][20][21][22][23][24][25][26], synchronization [27,28], and so on, in which both delay-independent and delay-dependent results are involved. Because of making use of the length of delay, delay-dependent results are less conservative, especially when time delay is small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that, as in the nondelay case, the “completion of squares” method can be used for a class of linear‐quadratic (LQ) problems with the linear SDDE and the quadratic cost . Furthermore, the stabilization of the SDDE was considered by Song et al, and the LMI conditions for H ∞ control of the linear SDDE was identified by Yang et al The H ∞ control problem for the linear SDDE with perturbation was studied by Li and Yang …”
Section: Introductionmentioning
confidence: 99%
“…14 We also note that, as in the nondelay case, the "completion of squares" method can be used for a class of linear-quadratic (LQ) problems with the linear SDDE and the quadratic cost. 15 Furthermore, the stabilization of the SDDE was considered by Song et al, 16 and the LMI conditions for H ∞ control of the linear SDDE was identified by Yang et al 17 The H ∞ control problem for the linear SDDE with perturbation was studied by Li and Yang. 18 We note that the stochastic optimal control and differential games for SDDEs studied in the references mentioned above can be regarded as risk-neutral since the corresponding objective functional involves only the first moment of the integral cost.…”
mentioning
confidence: 99%